Application of decellularization methods for scaffold production: advantages, disadvantages, biosafety and modifications - Shevchuk, O. I.; Korcheva, V. V.; Moskalenko, N. S.; Kyryk, V. M.; Kot, K. V.; Krasnienkov, D. S. (Frontiers in Bioengineering and Biotechnology, 2025)
The development of efficient, biocompatible scaffolds is an actual challenge in tissue engineering. Scaffolds derived from animal sources offer promising structural and biochemical properties but require thorough decellularization to minimize immunogenicity and maintain extracellular matrix integrity. Effective decellularization requires a synergistic combination of methods to ensure complete removal of immunogenic cellular components while preserving critical extracellular matrix elements such as glycosaminoglycans, collagens, and growth factors. This review covers the application of some decellularization methods (physical, chemical) in scaffold production, highlighting their respective advantages, limitations, and biosafety considerations. Moreover, the importance of scaffold sterilization: both physical techniques like gamma irradiation and chemical agents–are mentioned for their efficacy and cytotoxic risks. Furthermore, scaffold modifications, particularly recellularization strategies, are discussed as key enhancements to improve biocompatibility and functional integration. Overall, the selection and optimization of decellularization protocols are crucial for the safe and effective clinical implementation of bioengineered scaffolds.